The association between depression, Quality of life, and the Health care expenditure of patients with diabetes mellitus in Uganda - Akena, Dickens; Kadama, Philippa; Ashaba, Scholastic; Akello, Carolyne; Kwesiga, Brendan; Rejania, Lalitha; Okello, James; Mwesiga, Emmanuel. K.; Obuku, Ekwaro. A. (Journal of Affective Disorders, 2015)
Background—Depression is one of the commonest neuropsychiatric disorders in patients with diabetes mellitus (DM) and is associated with poor glycaemic control, vascular complications, a low quality of life and increased health care expenditure. Co-morbid DM and depression remains poorly identified and inadequately treated in sub-Saharan Africa. Methods—We conducted a cross-sectional survey of 437 patients with DM at 3 DM clinics in Uganda. Participants were assessed for depression, blood sugar levels, diabetic neuropathy, quality of life, and health care expenditures. Results—The prevalence of depression was 34.8%. Depressed participants were more likely to be suicidal [OR=3.81, (CI 2.87–5.04)], younger [OR=3.98 CI (1.20–13.23)], un-employed [OR=1.99(CI 1.04–3.81)], and having lost a spouse [OR=2.36 (CI 1.29–4.31)]. Overall quality of life was poor [OR=0.67 (CI 0.47–0.96)], they scored poorer in the physical [OR=0.97, (CI 0.95–0.99)], psychological [OR=1.05 (CI 1.03–1.07)], and environmental [OR=0.97, (CI 0.95–0.99)] domains. They had an increased likelihood of incurring direct out-of-pocket payments for health care services [OR=1.56 (CI 1.03–2.36)], and were more likely to be impoverished [OR=1.52 (CI 1.01–2.28)]. Limitation—The cross sectional nature of this study makes it difficult to examine causation. More studies are required in order to better understand the associations and impact of the factors examined above on patient outcomes. Conclusions—Depression is highly prevalent among patients with DM in Uganda, and is associated with a number of adverse outcomes. A holistic approach that focuses on the depression management among patients with diabetes is recommended.
Keywords: Depression; Quality of life; Health care expenditure of; Expenditure; Diabetes mellitus; Uganda